The Community of Inquiry framework as learning design model: a case study in postgraduate online education - Candace R. Nolan-Grant (Association for Learning Technology, 2019)
Interaction within online educational environments has long been advocated as conducive to learning, whether interaction between the learner and their teacher, the learner and online resources or the learner and their peers. The relationship among these three types of interaction is also receiving increasing attention, with the Community of Inquiry (CoI) framework providing a method of interpreting this relationship in terms of the interplay of teaching presence, cognitive presence and social presence. This case study investigates the use of the CoI framework as a learning design model, showing how it was used to address specific issues in a postgraduate online module. Specifically, the framework informed decisions to strongly link together interaction with the video content, activity on discussion boards and release of new learning materials. Using discussion board posts and video analytics as the primary evidence of learner engagement, the findings show how learner activity significantly increased in both 'social' contexts and 'cognitive' contexts. More importantly, analysis also revealed strong correlations among participation in discussions, video viewing and module completion. The study suggests that the CoI framework is a robust model for learning design in online environments.